Intellectual property rights, private investment in research, and productivity growth in Indian agriculture: A review of evidence and options - Kolady, Deepthi Elizabeth; Spielman, David J.; Cavalieri, Anthony J. (International Food Policy Research Institute, 2010)
With the growth of private investment in developing-country agriculture, new advances in the biological sciences, and rapid integration of developing countries into the global trading system, intellectual property rights (IPRs) have become an important concern for policymakers, corporate decisionmakers, and many other players in the agricultural sector. But there are still unanswered questions about whether emerging and evolving IPR regimes in developing countries will contribute to increasing agricultural productivity and improving food security. This paper attempts to answer some of these questions by tracing the effects of IPRs on private investment in crop genetic improvement and, in turn, on agricultural productivity. The paper focuses specifically on the case of India, the regional leader in implementing IPRs in agriculture. Findings indicate that maize and pearl millet yields grew significantly during the last two decades due to the combination of (1) public policies that encouraged private investment in India's seed industry during the 1980s, (2) public investment in hybrid breeding programs that generated new materials offering substantial yield gains, and (3) biological IPRs conferred by hybridization that conveniently married the private sector's need for appropriability with the nation's need for productivity growth. Although past lessons are not an indication of future success, this convergence of policy solutions and technology opportunities can be replicated for other crops that are vital to India's food security.